A PENINGKATAN KESADARAN GAYA HIDUP SEHAT MELALUI SKRINING DAN EDUKASI HIPERTENSI BAGI LANSIA DI POSYANDU - Upus Piatun Khodijah; Jecklyn Shindy Temartenan, Jecklyn Shindy Temartenan; Okti Rahayu Asih; Evy Nurachma (Komunikasi, 2025)
Hypertension is a non-communicable disease with a high prevalence, often referred to as a “silent killer” because most cases go undetected. In Indonesia, the prevalence of hypertension reaches 34.1% and increases significantly among the elderly population. Low awareness of routine check-ups, particularly in rural areas, heightens the risk of severe complications. This community service program aimed to raise awareness of healthy lifestyles through hypertension screening and education for the elderly in a village in West Java. The program was carried out using a participatory approach involving older adults, community health volunteers (posyandu cadres), healthcare workers, and village officials. A total of 52 elderly participants underwent blood pressure screening, which revealed that 40.4% were normal, 34.6% were pre-hypertensive, and 25.0% had hypertension. These findings highlight that nearly 60% of participants were either at risk or already suffering from hypertension.Interactive health education using simple media proved effective, as demonstrated by an increase in knowledge levels from 28.8% before the program to 75.0% after. The level of participation was also high, with 88.5% of elderly participants actively engaging in discussions. The involvement of posyandu cadres further strengthened the program by supporting routine monitoring and reinforcing healthy lifestyle reminders. This initiative successfully enhanced early detection, knowledge, and awareness among the elderly in preventing and managing hypertension.